A Colonial Expedition? French Soldiers' Experience at the Dardanelles. (2nd October 2019) - Horne, John
Abstract : As many French soldiers as ANZACs fought at Gallipoli. Their preconceptions had more to do with colonial campaigning than with the dominant French experience of the Great War — mass mobilisation to defend the nation on home territory. Moreover, a significant proportion of the troops at the Dardanelles were colonial. Yet the French soldiers discovered at Gallipoli a 'front' that was part of the mutual siege that ringed Europe and that bore more than a passing resemblance to the front in France. The article explores the experiences and perceptions of the French soldiers facing this paradox.